Design of controller for boost converter to regulate voltage output - Aminudin Anuar (School of Electrical Systems Engineering, Universiti Malaysia Perlis, 2015)
Capacitor can be used as an energy storage element to supply small power in replacing a battery. The advantage of using capacitor is the charging time is much faster than charging a battery. But the disadvantage is that the capacitor voltage value is not constant to supply a load. From that, a dissertation project has been conducted to design a controller using boost converter to regulate the capacitor voltage output.